“A Woman Who is Dead”: The Tragedy, Transgression, and Religiousness of Oscar Wilde’s Salome - Ana Carolina Vilalta Caetano (ABEI Journal, 2023)
This article aims at analysing Oscar Wilde’s play Salome (1891) under the lens of Georges Bataille’s theory of transgression and eroticism, and the notion of eros present in archaic Greek lyric poetry. Salome takes place in Herod Antipas’ palace during the night of a banquet and follows the court and the royal family as the event unfolds into tragedy. The Tetrarch has Jokanaan, a prophet announcing the return of the Messiah, imprisoned in a cistern. His step-daughter, Salome, fascinated by the prophet’s voice and by his loud sermons, convinces the guards to allow her to see him. She immediately falls in love, but Jokanaan is unresponsive to her advances, which ultimately causes her to manipulate the Tetrarch and commit a heinous crime in order to be united with her beloved. In order to fully explain Wilde’s use of religion as a background to make a case for the physical, then, the fin de siècle Romantic femme fatale is briefly introduced alongside the Symbolist transcendental ideal. Thus, Salome is analysed as a character that surpasses her tragic role and becomes associated with concepts such as abject femininity, coined by psychoanalyst Julia Kristeva.